O segredo do sucesso escolar: contributo da web 2.0 - Baptista, Zélia Maria de Oliveira (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Performance evaluation of Macao governmental web portal - Cordova, Vicente Jorge (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Ensino-aprendizagem da matemática: que lugar a mitos? que lugar a Macau? - Oliveira, Maria de Fátima Andrade de (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Re-conceptualising computer literacy teaching and learning using constructivist principles and peer-tutoring - Wong, Kin Ming (University of Saint Joseph, 2015)
Nowadays, many university students (in Macau) are required to attend computer literacy courses to develop their basic skill levels and knowledge as part of their literacy foundation requirements. To be effective, such courses, which are very staff intensive and require access to expensive equipment and software, necessitate high levels of individual teaching. Evidence gathered at two study sites during this research, strongly suggests that many students may not be benefiting sufficiently from their computer literacy courses. Teachers frequently complain about the weak IT skills of many course graduates. This research proposes an innovative model for designing and delivering computer literacy courses based on constructivist principles, using peer-tutoring and blended learning to increase cost effectiveness and to improve student outcomes. Central to the model being proposed is the training and deployment of former course graduates as peer instructors and assessors. Constructivist principles provide a conceptual framework to ensure that the curriculum content, teaching strategies, learning styles and assessment procedures are properly aligned and fully understood by both the instructors and students to achieve high quality learning outcomes. An action research approach was used during the pilot and trail phases of the research to monitor the implementation of the model and evaluate its effectiveness using mixed methods. The planned two–phase action evaluation used a questionnaire to investigate the effectiveness of knowledge and skill transfer to students, and tutors’ learning progress; in-depth semi-structured interviews were used to survey, interpret and evaluate students’ and tutors’ perceptions of the new teaching and learning approach. Most respondents had a Confucian Heritage Cultural Background. For the first time, the research provides new insights into ways in which Confucian Heritage Cultural factors, interact with constructive principles in developing peer-tutoring methods in a university setting inMacau, and more widely
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Implementation of item response theory to English grammar assessment to map students' understanding and to foster learning - Ho, U. Kei (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Improving Students' Reading Literacy with the Guided Use of a Digital Reading Platform in a Chinese Primary School - Norte, Patricia Alexandra D. C. (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

English as a foreign language: a comprehensive study on teacher's self-efficacy and its antecedents in Macao - Lam, Man Ieng; Malungu, Laurie Baker; Negreiros, João Garrott Marques (University of Saint Joseph, 2019)
As societies globalize, mastery of a second or multiple languages has become an important index to enhance interaction in the society. In that English is a is a widely used medium of communication globally for engagement in international business, commerce, science, technology and governance, the benefits of an efficacious English language teaching force to facilitate the English acquisition process of students in classrooms around the world is highly valued. For the purpose of this study, the English language teacher efficacy instrument (ELTEI) was adapted to the local context to measure the professional efficacy of the English as a foreign language (EFL) teacher participants. The objective of the research was to investigate the degree of relationship between antecedent conditions and specific teacher efficacy in Macao. A mixed-method approach in a sequential phase design was adopted to explore the efficacy of English language teachers serving Chinese medium schools in a non-English speaking region in Asia. Phase-one employed a qualitative approach to contextualize the measurement instrument and to ascertain important characteristics of the target population. Phase-two ensured a quantitative approach to yield understanding regarding the influence of key antecedent conditions on the efficacy of English language teachers in Macao. As evidenced through multiple linear regressions and structural equation modeling, openness, neuroticism, and perceived school support were significant predictors for teacher’s self-efficacy in English teaching. Recommendations for the school management to enhance and sustain the efficacy of EFL teachers in Macao were discussed
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Enhancing Learning of Accounting for Non-Accounting students: Through Lens of Theory of Planned Behavior and Experiential Learning Styles - Lau, Meng Chan (University of Saint Joseph, 2020)
This thesis aims to explore how learning accounting for non-accounting major students could be enhanced through a comprehensive framework connecting individual attributes and learning approaches. While accounting is considered an important and mandatory discipline for business students, it is also considered a difficult subject which deters students’ engagement in the subject. Although the issue has been widely recognized, there are relatively less discussions on possible remedies. Learning accounting is a dynamic process that go beyond the traditional one-to-many learning and teaching settings, all factors revolving the students’ learning environment and process, altogether determine and affect the learning efficiencies. A meta-analysis was first performed to understand the standings of accounting education and to identify gaps within existing literatures in the field of management, accounting, tourism and general education researches. A documentary review on the curricula of all Macau HEI programs involving compulsory accounting courses was also conducted to understand the role and significance of accounting courses for non-accounting college students in Macau. Based on the literature review, this study borrows constructs from theory of planned behavior (TPB) models in its research framework. It attempts to provide a comprehensive framework to understand how students learn accounting efficiently by delving into individual learning styles of the students and their perceived helpfulness and self-efficacy, in respective to different learning techniques. Due to its exploratory nature, a mixed method of qualitative and quantitative methodology is adopted, where both focus group discussions and in-depth interviews are performed with non-accounting students to elicit understandings on student’s difficulties in learning accounting and their preferences for different learning styles. Then, a full-scale quantitative survey is conducted in a Macau higher education institute to assess the learning efficiencies of accounting in different situations. A triangulation with feedback from faculties and administrators are also elicited to provide alternate dimensions on the issues. With no surprise, there is no one best 3 teaching style or method for all students, this thesis contributes to accounting education research by provide a comprehensive diagnosis on the all-round learning stimulus and hindrance in learning accounting. At the end, recommendations are provided for accounting educators to emphasize on the uniqueness of students and to encourage a more dynamic and open environment for learning. Limitations of the studies are also discussed
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph